PERANAN MODERASI FAKTOR EKSTERNAL DALAM HUBUNGAN SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL DENGAN KUALITAS INFORMASI LAPORAN KEUANGAN - Nafi' Inayati Zahro (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2016)
This study aims to analyze accounting information system and internal control system to the state and local government financial statement quality, also examine the accounting information system and internal control system to the state and local government financial statement quality are more significant if external factors are input as a moderation variabel. The sampel of this research are taken by purposive sampling, the respondents are staff on the unit of work of the office of financial management and assets (DPKAD) and office of the revenue and the financial management area (DPPKD) of the regency at Patieks-residence. The hyphothesis are examine by Moderated Regression Analysis (MRA). The result of this research show that there are effect of the accounting information system and internal control system on the state and local government financial statement quality, but the external factors fail as a moderated variable. Key words: accounting, information, statement, control, system